2018
DOI: 10.1111/ter.12317
|View full text |Cite
|
Sign up to set email alerts
|

Non‐uniform splitting of a single mantle plume by double cratonic roots: Insight into the origin of the central and southern East African Rift System

Abstract: To cite this version:Alexander Koptev, Sierd Cloetingh, Taras Gerya, Eric Calais, Sylvie Leroy. Non-uniform splitting of a single mantle plume by double cratonic roots: Insight into the origin of the central and southern East African Rift System. Terra Nova, Wiley-Blackwell, 2017, 30 (2)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 90 publications
3
30
0
Order By: Relevance
“…A slightly more complex model setup, with a craton embedded in the EARS lithosphere (model 10), is shown on Figure . Similarly to previous 3‐D experiments (Burov & Gerya, ; Koptev et al, , , ), this model predicts a rapid mantle ascent (vertical speed of ~80 cm/yr) with the plume head reaching the base of the lithosphere 0.5 Myr into the model evolution. The plume material is then deflected to the eastern side of the craton, where it generates a broad topographic high reaching a maximum of 2 km similar in spatial extent to the Kenya dome of the central EARS (Figure ).…”
Section: Resultssupporting
confidence: 79%
“…A slightly more complex model setup, with a craton embedded in the EARS lithosphere (model 10), is shown on Figure . Similarly to previous 3‐D experiments (Burov & Gerya, ; Koptev et al, , , ), this model predicts a rapid mantle ascent (vertical speed of ~80 cm/yr) with the plume head reaching the base of the lithosphere 0.5 Myr into the model evolution. The plume material is then deflected to the eastern side of the craton, where it generates a broad topographic high reaching a maximum of 2 km similar in spatial extent to the Kenya dome of the central EARS (Figure ).…”
Section: Resultssupporting
confidence: 79%
“…Recent results of spherical shell finite element modelling of regional stress and strain field in Africa has shown that compressional stresses applied at the mid-ocean ridges surrounding Africa result in rift-perpendicular deviatoric extension in the East African rift valleys that, being combined with upwelling mantle plume(s), leads to localization of extensional deformation and explains the initial lithosphere break-up in the East Africa and the Afar 32 . Likewise, recent 3D thermo-mechanical deformation models show that pre-stressed lithosphere subjected to EW extension is a necessary initial condition for plume-induced localized rifts to develop in the central part of the East African Rift 8 , 9 , 33 .…”
Section: A Type-locale For Triple Junctions: the Afar Regionmentioning
confidence: 98%
“…The EARS represents an ideal laboratory for studying magma-poor rifting because it comprises the two contrasting magmatic styles of rifting with the eastern branch being magma rich and the western branch being magma poor [ Figure 1; Koptev et al, 2015Koptev et al, , 2018 and references therein]. The western branch includes rift segments, such as the Malawi Rift, that are considered well developed in terms of morphological expression yet have only isolated zones of magmatism.…”
Section: Introductionmentioning
confidence: 99%